2006
DOI: 10.1007/s10755-006-9031-7
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Creating Engaged Land-Grant Universities: Penn State’s Engagement Ladder Model

Abstract: The original mission of the state and land-grant university was to engage with communities to solve problems and improve the quality of life for the citizenry. Today most state and land-grant universities have moved far away from their original mission and are struggling to become engaged with the communities they serve. In this case study, we highlight some of the steady progress toward engagement that has recently occurred at The Pennsylvania State University. We catalogue how strong vision and leadership; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Our review of the literature on the scholarship of engagement identified five major strands: (1) universities defining or redefining their engagement missions (Aronson and Webster 2007;Brabeck et al 1998;Lerner and Simon 1998;Percy et al 2006); (2) community-campus partnerships as a means of enriching the educational experiences of university students (e.g., service learning and internships; Allen-Gil et al 2005;Benson et al 2000;Dorado and Giles 2004); (3) universities engaged in community development efforts in partnership with their surrounding neighborhoods (Boyle and Silver 2005;Wiewel and Guerrero 1998); (4) university scholars and community members coming together to address issues of mutual interest (i.e., community-based research and service projects; Lamb-Parker et al 2002;Lantz et al 2001;Walsh 2006); and (5) measurement of the characteristics and consequences of community-university partnership (e.g., group dynamics, degree of collaboration, etc. ; El-Ansari 1999;El-Ansari et al 2001;El-Ansari and Weiss 2006;Granner and Sharpe 2004;Schulz et al 2003).…”
mentioning
confidence: 99%
“…Our review of the literature on the scholarship of engagement identified five major strands: (1) universities defining or redefining their engagement missions (Aronson and Webster 2007;Brabeck et al 1998;Lerner and Simon 1998;Percy et al 2006); (2) community-campus partnerships as a means of enriching the educational experiences of university students (e.g., service learning and internships; Allen-Gil et al 2005;Benson et al 2000;Dorado and Giles 2004); (3) universities engaged in community development efforts in partnership with their surrounding neighborhoods (Boyle and Silver 2005;Wiewel and Guerrero 1998); (4) university scholars and community members coming together to address issues of mutual interest (i.e., community-based research and service projects; Lamb-Parker et al 2002;Lantz et al 2001;Walsh 2006); and (5) measurement of the characteristics and consequences of community-university partnership (e.g., group dynamics, degree of collaboration, etc. ; El-Ansari 1999;El-Ansari et al 2001;El-Ansari and Weiss 2006;Granner and Sharpe 2004;Schulz et al 2003).…”
mentioning
confidence: 99%
“…The fundamental purpose of land-grant universities was not just to provide skills to farmers through training but to develop new and innovative knowledge whose application would transform agriculture at the time (Gavazzi 2020). They were expected to develop and implement research-based programmes and educational resources with the goal of improving the lives of the individuals, families, and communities within the state (Aronson and Webster 2007).…”
Section: Leveraging University Resources and Expertise For The Greate...mentioning
confidence: 99%
“…Several authors (Al-Kodmany 1999;Allen-Meares et al 2005;Amey et al 2002;Arbuckle and DeHoog 2004;Altman 1995;Barnett 1993;Percy, Zimpher and Brukardt 2007) argue that universities are actively willing to participate in the betterment of their communities and are developing strategies for addressing social issues in their communities through collaborative approaches. Various other authors (Aronson and Webster 2007;Buys and Burnall 2007;Chibucos and Lerner 1999) suggest that this return of universities towards their service-focused mission would have positive repercussions for both universities and communities.…”
Section: Introductionmentioning
confidence: 98%